Fixed drug eruption due to levocetirizine - Jhaj, Ratinder (J Pharmacol Pharmacother, 2016)
A fixed drug eruption (FDE) is a cutaneous adverse drug reaction due to Type IV or delayed cell-mediated hypersensitivity. Antihistamines, which antagonize the action of histamine during an allergic reaction by blocking the H(1) histamine receptors, are used routinely for the treatment of various allergic disorders such as urticaria, eczemas, and also in itchy lesions of skin like scabies. Levocetirizine, an active (R)-enantiomer of cetirizine, is a newer or second generation antihistamine, with more specific actions and fewer side effects, including cutaneous reactions. FDE due to levocetirizine as well as with cetirizine are rare. We report a case of levocetirizine induced FDE in a 49-year-old male patient with scabies. The patient had a history of cetirizine induced FDE in the past.